Implementation of 3Rs in enterprises in Vietnam as one of the most dynamic emerging countries in South East Asia region - Nguyễn Thanh Xuân VI; Nguyễn Thị Bích Liễu (My University, 2018)
Implementation of 3Rs in enterprises in Vietnam as one of the most dynamic emerging countries in South East Asia region
Keywords: 3Rs implementation; Sustainable enterprise; Vietnam